PV Array Based Smart Home Automation System - Şenpınar, A. (My University, 2018)
The utilization of renewable energy sources have been increasing day by day. Solar, wind, biomass, wave, etc. are some of the renewable energy sources. Solar, wind and hydro are more commonly used than others. Solar energy has many advantages such as abundance, renewability, continuation, and pollution free etc. Advancing technology increases people’s life standards. Over time, high life standards have stopped being a luxury and entered people’s homes with smart home automation systems. With the advances in Internet technologies, people now expect to be able to control their homes and workplaces over the Internet too. This study controls six different Computer/Internet-based systems of smart home automation in a house which is included solar arrays. These systems were illumination of three different rooms, temperature control of a room, garden irrigation system control, and home security system control. With the software written, all these systems were monitored online on a website. These controls were successfully experimented on the model house with the smart home automation system designed.
Keywords: Mühendislik; Elektrik ve Elektronik; Yeşil; Sürdürülebilir Bilim ve Teknoloji; Enerji ve Yakıtlar